2009
DOI: 10.1002/pssa.200881460
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation nucleation from surface step in silicon: The glide set versus the shuffle set

Abstract: We have studied the mechanisms of dislocation nucleation from surface defects in silicon submitted to various stresses and temperatures. Molecular dynamics simulations with three classical potentials have shown the existence of two different plastic modes in silicon which can be activated from surfaces. At high temperatures and low stresses dislocations nucleation occurs in the {111} glide set planes, while at low temperatures and large stresses it occurs in the {111} shuffle set planes. The analysis of disloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…For example, recent molecular dynamics simulations of silicon nanostructures submitted to various stresses and temperatures revealed a transition in the onset of silicon plasticity [26,27]: at high temperature and low stress, partial dislocation loops are nucleated in the glide set planes, but at low temperature and very high stress, perfect dislocation loops are formed in the shuffle set. This observation suggested that plasticity in silicon nanostructures could be controlled by dislocation nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent molecular dynamics simulations of silicon nanostructures submitted to various stresses and temperatures revealed a transition in the onset of silicon plasticity [26,27]: at high temperature and low stress, partial dislocation loops are nucleated in the glide set planes, but at low temperature and very high stress, perfect dislocation loops are formed in the shuffle set. This observation suggested that plasticity in silicon nanostructures could be controlled by dislocation nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…This size effect cannot be explained by the initial defects density like in metals (), because Si nanoobjects can be grown without residual defects. In these conditions, crack formation should take origin at the surface as it has been shown for dislocations ().…”
Section: Introductionmentioning
confidence: 79%
“…a) and can act as stress concentrators for the dislocation nucleation. In particular on the (100) surface the dimers formation can be viewed as surface steps that are well known to favor dislocation nucleation . The formation of a surface defect appears then as the main parameter governing dislocation nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the temperature does not allow the glide set planes to be involved (unlike in experiments), this was supposed to be due to the limited number of atoms in the simulation box which prevents the formation of kink pairs. In recent simulations the number of atoms was increased up to 1.5×10 4 especially along the step providing remarkable results [16] which can be summarized as follows:…”
Section: Generation At the Interface Or Within The Filmmentioning
confidence: 95%
“…3.1 Simulation of dislocation nucleation from surface step This approach was mainly developed by the group of the University of Poitiers (France) [14][15][16]. It consists in studying by atomic simulation the extended defects which can be emitted by a surface step on the (100) surface of Si and parallel to <011> under uniaxial stress (tension or compression).…”
Section: Generation At the Interface Or Within The Filmmentioning
confidence: 99%